Metabolite Mitigates Resistance (Molecular Medicine Communications, 2021)
A growing problem that is yet to be properly addressed is the conferment of antibiotic resistance. Zhao et al. showed that in pathogenic Gram-negative bacteria, increased influx and efficacy of antibiotics was seen with the use of glutamine. The mechanism involves alteration of the metabolism of nucleotides causing the bacterial membrane to have increased non-selective permeability in bacterial strains possessing diverse resistance mechanisms. In mouse models with systemic or biofilm infections, enhanced antibiotic efficacy was seen with glutamine supplementation further strengthening its potential use. Sci Transl Med. 2021 Dec 22;13(625):eabj0716.